2018
DOI: 10.2340/00015555-2780
|View full text |Cite
|
Sign up to set email alerts
|

Role of Substance P and Its Receptor Neurokinin 1 in Chronic Prurigo: A Randomized, Proof-of-Concept, Controlled Trial with Topical Aprepitant

Abstract: Substance P (SP) and its receptor neurokinin 1 (NK1R) are thought to be involved in the pathogenesis of chronic prurigo. Here, we assessed SP serum levels, cutaneous NK1R expression, and the effects of topical aprepitant, an NK1R antagonist, in patients with chronic prurigo. SP and NK1R were increased, compared with controls, in the serum and in lesional vs. non-lesional skin of the patients, respectively. Aprepitant, in a randomized, placebo-controlled, split-sided, doubleblind trial, reduced the intensity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 0 publications
4
45
0
7
Order By: Relevance
“…Interestingly, we found that the NK1R is up‐regulated in PN even before the therapy compared to healthy controls. This is in line with published data were chronic pruritus patients show higher NK1R expression compared to healthy controls in peripheral blood but has not yet been shown to be relevant in the skin of these patient, too. On the one hand, this supports the important role of the receptor in pruritic diseases such as PN but, on the other hand, does not explain the antipruritic effect by itself.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, we found that the NK1R is up‐regulated in PN even before the therapy compared to healthy controls. This is in line with published data were chronic pruritus patients show higher NK1R expression compared to healthy controls in peripheral blood but has not yet been shown to be relevant in the skin of these patient, too. On the one hand, this supports the important role of the receptor in pruritic diseases such as PN but, on the other hand, does not explain the antipruritic effect by itself.…”
Section: Discussionsupporting
confidence: 91%
“…Aprepitant was frequently supposed to mediate effects in the skin . But, both, topical and systemic application, have been also reported to be insufficient for successful treatment in other studies …”
Section: Discussionmentioning
confidence: 99%
“…Neurokinin 1 receptor antagonism with aprepitant can lead to a reduction of itch intensity in patients suffering from chronic pruritus . Whether the effect of the drug is central, peripheral or both, remains to be determined as the effect of topical aprepitant was matched by the vehicle . Additional NK 1 R antagonists are now being evaluated and early clinical reports from industry, although not peer‐reviewed, are promising.…”
Section: Itch Mediators and Receptors With Links To Mast Cells And Bamentioning
confidence: 99%
“…The effectiveness of NK1 antagonists for the treatment of chronic itch is under intense investigation. Promising data have been generated but the failure of topical aprepitant relative to vehicle suggests that therapeutic benefit may arise from targeting central NK1. Moreover, NK1 mutant mice still scratched when injected with SP.…”
Section: Itch Mediators and Receptors With Links To Mast Cells And Bamentioning
confidence: 99%
See 1 more Smart Citation